Pinecraft refuge [large type] - Worth, Lenora (Worth, Lenora Pinecraft Seasons, 2023)
"When her doctor prescribes fresh air and sunshine, Eva Miller turns her Florida getaway into a chance to gain some independence. Only, working part-time for Amish shop owner Tanner Dawson is hardly a vacation. The overprotective single father reminds Eva of her own strict upbringing. But as she begins to see beneath his gruff exterior, can she trust Tanner--and her heart--enough to stay?"--